If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + 6) = 9x + 46 Reorder the terms: 8(6 + x) = 9x + 46 (6 * 8 + x * 8) = 9x + 46 (48 + 8x) = 9x + 46 Reorder the terms: 48 + 8x = 46 + 9x Solving 48 + 8x = 46 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 48 + 8x + -9x = 46 + 9x + -9x Combine like terms: 8x + -9x = -1x 48 + -1x = 46 + 9x + -9x Combine like terms: 9x + -9x = 0 48 + -1x = 46 + 0 48 + -1x = 46 Add '-48' to each side of the equation. 48 + -48 + -1x = 46 + -48 Combine like terms: 48 + -48 = 0 0 + -1x = 46 + -48 -1x = 46 + -48 Combine like terms: 46 + -48 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2
| 33=y+3-0.4 | | 5x-3=-3+4x | | 107-4x=23x+20 | | 7(x+3)=10x+9 | | 13=K+8-2 | | 6b-3=11b-3-5b | | 6x+12-2x+14= | | 6x+14x=90 | | 3(x-6)=8x-58 | | 8t-4=44 | | x-6=4x+12 | | 8t-4=4 | | 3y+6y+2=10 | | (2x+3x+5x)-6x=0 | | M(2p-7q)= | | 3(x-6)=9x-36 | | (9x-x)=5 | | 5(3c-2d)= | | 8Xn=63 | | 6(x-7)=3x-36 | | 3a^2-19a-40=0 | | h=99t-16t^2 | | 2cosx=0 | | 2cos(x)=0 | | x(2x-3)+x(4x-6)=(6x+5)(x-4) | | 16=-2c+16 | | 2cos(10x)=0 | | x=1y=1 | | 2(x-4)=9x-57 | | 2(q-4)squared=50 | | x-4y=17fory | | -3w(w+5)(w-1)=0 |